Differential role of long terminal repeat control elements for the regulation of basal and Tat-mediated transcription of the human immunodeficiency virus in stimulated and unstimulated primary human macrophages. - Moses, A V (1994)
Primary human macrophages induced to differentiate through contact with autologous activated nonadherent cells were used to investigate the transcriptional mechanisms involved in reactivation of human immunodeficiency virus (HIV) replication. Through transient transfection experiments with an HIV long terminal repeat (LTR)-chloramphenicol acetyltransferase reporter construct, we show that macrophage differentiation results in a 20-fold upregulation of basal LTR activity. To identify sequence elements responsive to the differentiation process, point mutations introduced into the LTR were tested in differentiated and undifferentiated macrophages. Several elements were identified as positive regulators of basal transcription. TATA, Sp1, and NF-kappa B binding sites were the most influential. The low-affinity site for LBP-1 (UBP-1) functioned as a negative regulator of LTR activity in undifferentiated macrophages, but this influence was lost upon differentiation. When tat was cotransfected into the expression system, the requirement for LTR elements identified as important for positive regulation of basal transcription remained in undifferentiated macrophages. Interestingly, however, the mutations in positive control elements which debilitated activity in undifferentiated macrophages had no effect on LTR activity in differentiated macrophages. Thus, it appears that while HIV-LTR activity is highly dependent on cellular transcription factors in undifferentiated cells, in differentiated macrophages the viral protein Tat confers pliability on the LTR and facilitates autonomy from absolute cellular control mechanisms. In vivo, release from either positive or negative regulation via cellular proteins may facilitate reactivation of HIV in macrophages.